2023
DOI: 10.3389/fpubh.2023.1047391
|View full text |Cite
|
Sign up to set email alerts
|

Risk of peripheral facial palsy following parenteral inactivated influenza vaccination in the elderly Chinese population

Abstract: BackgroundConcern about the risk of peripheral facial palsy (PFP) following vaccination is one reason for hesitancy in influenza vaccination. However, the association between the flu vaccine and PFP is still controversial, and further evidence is urgently needed.MethodsThis self-controlled case series study evaluated PFP risk following inactivated influenza vaccine in the elderly using a large linked database in Ningbo, China. Relative incidence ratios (RIRs) and 95% confidence intervals (CIs) estimated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In this study, the NRHIP provided each participant basic demographic information, disease diagnoses, influenza test information, and vaccination records. Multiple studies have demonstrated the reliability and accuracy of the data sources [ 14 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the NRHIP provided each participant basic demographic information, disease diagnoses, influenza test information, and vaccination records. Multiple studies have demonstrated the reliability and accuracy of the data sources [ 14 16 ].…”
Section: Methodsmentioning
confidence: 99%